Revenants of the German Empire colonial Germans, imperialism, and the League of Nations - Wempe, Sean Andrew 1983- (Oxford University Press USA - OSO, 2019)
Framed by the 1919 Treaty of Versailles, the formation of the League of Nations Mandates System, the 1925 Locarno Conference, and the Manchurian Crisis of the early 1930s, Revenants of the German Empire: Colonial Germans, Imperialism, and the League of Nations explores the adaptiveness of German colonists after the loss of the German colonies following the First World War.